2011
DOI: 10.1007/s10008-011-1509-2
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical characterization of Prussian blue type nickel hexacyanoferrate redox mediator for potential application as charge relay in dye-sensitized solar cells

Abstract: A polynuclear electronically/ionically (redox) conducting mixed-valent inorganic material such as nickel (II) hexacyanoferrate(II,III), NiHCF, was considered for potential application as a redox mediator (charge relay) in dye-sensitized solar cell (DSSC). The NiHCF redox reactions were found fast and reversible not only when the system was studied as thin film exposed to an aqueous supporting electrolyte but also as bulk material (pasted powder) in solid state, i.e., in the absence of contact with external liq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 37 publications
0
13
0
2
Order By: Relevance
“…[6] Organic solution-processable CTMs also play a vital role in high-performance perovskite solar cells, affording power conversion efficiencies beyond 20%. [12,13] Very recently, copper phenanthroline complexes have been successfully applied as a hole transport material in dye-sensitized solar cells (DSCs), thus pointing to the general prospect of developing transition metal complexes as an emerging class of CTMs. [8,9] Traditionally these materials have been chosen for their superior light absorption and emission properties.…”
Section: Introductionmentioning
confidence: 99%
“…[6] Organic solution-processable CTMs also play a vital role in high-performance perovskite solar cells, affording power conversion efficiencies beyond 20%. [12,13] Very recently, copper phenanthroline complexes have been successfully applied as a hole transport material in dye-sensitized solar cells (DSCs), thus pointing to the general prospect of developing transition metal complexes as an emerging class of CTMs. [8,9] Traditionally these materials have been chosen for their superior light absorption and emission properties.…”
Section: Introductionmentioning
confidence: 99%
“…An additional study by Daenake, et al included the no-corrosive ferrocyanide complexes as redox mediators for aqueous media DSSC [181]. The redox potential reported for the complex Fe(CN) 6 4−/3− varies from 0.466 V versus SHE to 0.514 V versus SHE [182][183][184], depending on the electrolyte, and it is likely to reach higher U OC values than those obtained with iodide-based electrolytes. The high molar extinction coefficient of the carbazole dye MK-2 makes it appropriate for thin film sensitization.…”
Section: +mentioning
confidence: 99%
“…115 The same solar conversion efficiencies of 4.3-5.2% and also IPCE results were attained using Fc, Et 2 Fc and EtFc. 117 The current consensus is that water is an undesirable contaminant in DSSC electrolytes as it causes to the formation of iodate, dye desorption, low device efficiencies and device instability. In addition, their results indicated that Et 2 Fc, EtFc and Fc, promote fast dye regeneration by providing the driving forces of 35-46 kJ mol -1 .…”
mentioning
confidence: 99%